1985
DOI: 10.1177/019459988509300204
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Postoperative Growth Rates in Acoustic Neuromas Documented with CT Scanning

Abstract: Sequential computerized tomography (CT) allows us to determine the growth rate of acoustic neuromas. Prior to CT scanning, a variability in tumor growth rates was recognized on the basis of clinical signs. After incomplete tumor removal, some patients experienced rapid recurrence, whereas others lived many years without recurrence. We used CT scanning to study tumor growth rates in a heterogeneous group of 21 patients. Thirteen elderly patients were given annual scans after incomplete tumor removal, while eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0
4

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 3 publications
4
43
0
4
Order By: Relevance
“…The growth rate appears to be different before and after surgery [12]. Silverstein et al [10], have reported that 80% of the patients who underwent subtotal removal, show no postoperative growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth rate appears to be different before and after surgery [12]. Silverstein et al [10], have reported that 80% of the patients who underwent subtotal removal, show no postoperative growth.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports on the growth rate of AN have demonstrated slow growth prior to surgery [9,10,12]. The growth rate appears to be different before and after surgery [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La pérdida de asociación entre tamaño tumoral y mejores resultados de CV, la dificultad para establecer el tamaño tumoral que es suficiente para amenazar la vida del paciente o justificar una cirugía, el conocimiento de que algunos tumores permanecen estáticos o presentan ritmos de crecimiento muy lentos [104][105][106] , y nuestro actual hallazgo de una relación débil pero inversa entre la CV y el tamaño tumoral, implica que la elección del tratamiento quirúrgico frente a otras opciones y establecer el momento para llevarlo a cabo, se convierta en un desafío. Además, nos obliga a no asumir de forma categórica, y a desechar la idea tradicional de que pacientes intervenidos con tumores más pequeños verán afectada su CV en menor grado que aquellos con tumores grandes.…”
Section: Tamaño Tumoral Y Compresión De Troncounclassified
“…Geralmente tem cre s c i m e n t o lento, em média 1 a 5 mm por ano, e se originam na bainha do nervo vestibular perto da junção mielinoglial, próximo ao poro acústico interno. São tumore s bem circunscritos e encapsulados por epineuro [2][3][4] . Atualmente, a ressonância magnética (RM) e tomografia computadorizada (TC) são inadequadas para prever crescimento tumoral a não ser quando feitas de maneira seriada.…”
unclassified